Religion and the common good in a pluralistic society: Reformed theological perspectives - Coertzen, PC (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
This article is about religion and the common good in a pluralistic society. It is argued with the pluralistic society of South Africa in mind. The theme is further argued against the background of reformed theology and asks about the contribution that reformed theology can make towards the common good in a pluralistic society.